2019
DOI: 10.1186/s12877-019-1341-6
|View full text |Cite
|
Sign up to set email alerts
|

Community resource referral needs among African American dementia caregivers in an urban community: a qualitative study

Abstract: BackgroundAfrican American caregivers of community-residing persons with dementia are mostly unpaid and have high rates of unmet basic and health needs. The National Alzheimer’s Project Act (NAPA) mandates improved coordination of care for persons with dementia and calls for special attention to racial populations at higher risk for Alzheimer’s Disease or related dementias (ADRD) to decrease health disparities. The purpose of this study is to describe the perceptions of African American caregivers of people wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
0
20
0
10
Order By: Relevance
“…Participants in this study were aging in place in their communities before admission to the hospital. Studies have shown that African American families living in urban areas experience challenges in accessing supportive services related to dementia which may explain our findings of worse dementia-related outcomes at admission compared to their white counterparts (Abramsohn et al, 2019; Epps et al, 2018). Accessing culturally competent community-based health care can also be challenging (Clark et al, 2018).…”
Section: Discussionmentioning
confidence: 76%
“…Participants in this study were aging in place in their communities before admission to the hospital. Studies have shown that African American families living in urban areas experience challenges in accessing supportive services related to dementia which may explain our findings of worse dementia-related outcomes at admission compared to their white counterparts (Abramsohn et al, 2019; Epps et al, 2018). Accessing culturally competent community-based health care can also be challenging (Clark et al, 2018).…”
Section: Discussionmentioning
confidence: 76%
“…Efforts from the voluntary sectors have been particularly useful, as these organizations are positioned to be the bridge between the clinic and resources necessary to address social needs. For example, the NOWPOW program links together a patient's electronic health record with community-based databases to generate prescriptions for patients in need [10,13]. Also, there is great utility in expanding culturally competent practices, such as the use of interpreters and providing language-appropriate materials.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior study, the highest rated unmet need among caregivers (32% identifying as a race or ethnicity other than white) was for community resource referrals (90%) (Black et al, 2013). In an in-depth qualitative study of African American caregivers, we identified a need for places for socialization (both for themselves and for the care recipient) and for information about hospice services (Abramsohn et al, 2019). Caregivers also suggested including detailed eligibility criteria and an indication of services with providers who were trained in dementia care needs to improve delivery of clinical referrals to community resources.…”
Section: Introductionmentioning
confidence: 92%
“…A recent real-world trial of the impact of the HealtheRx among middle age and older adults (90% African American) demonstrated increased knowledge of and self-efficacy for finding community resources (Lindau et al, 2019;Tung et al, 2020). A HealtheRx for caregivers of persons with dementia ("HealtheRx-Dementia") was developed with input from African American caregivers who included social and selfcare resources and indication of a service's capability to care for persons with dementia (Abramsohn et al, 2019). This study extends this prior work and aims to evaluate the experience of caregivers from other racial and ethnic minority groups, including Hispanic and Asian caregivers, and garner their feedback on the HealtheRx-Dementia.…”
Section: Introductionmentioning
confidence: 99%